Flooding Stress and High-Pressure Treatment Enhance the GABA Content of the Vegetable Soybean (Glycine max Merr.) - Man-Shin Shiu; Yuan-Tay Shyu; Sz-Jie Wu (Agriculture, 2020)
γ-aminobutyric acid (GABA) is the chief inhibitory neurotransmitter in the central nervous system and of substantial physiological significance to mammals. The GABA content of plants is generally low; however, it increases significantly when plants encounter stress. The present study investigates the effects of flooding stress and high-pressure processing on GABA content enrichment in the vegetable soybean (Glycine max Merr.) cultivar Kaohsiung No. 9 and potential mechanisms. Results indicate that flooding stress increased the GABA content of vegetable soybean kernels, with the possible mechanism involving the upregulation of glutamic acid decarboxylase 5 (GAD5) and aminoaldehyde dehydrogenase (AMADH) and downregulation of succinate semialdehyde dehydrogenase (SSADH). High-pressure treatment increased the GABA content through increased GAD activity. A specific combination of flooding stress, high-pressure treatment, and storage treatment enhanced vegetable soybean GABA content up to 696.6 ± 65.7 mg/100 g. Flooding treatment prior to harvesting did not cause differences in consumption quality. These results show that flooding stress and high pressure treatment can increase GABA content and enhance the functional value of the vegetable soybean cultivar Kaohsiung No. 9.